Depth Profiling of Strain in Textured Tungsten Films. (10th January 2018) - Baldinozzi, Gianguido; Lecoeur, Philippe; Pontikis, Vassilis
ABSTRACT: Development of materials and engineering solutions in fusion technologies supports the use of high-Z elements as Plasma Facing Component to avoid tritium deposition with carbon. Tungsten is among the most promising candidates for these applications. Therefore, research in this area has gained increasing attention. It is then important to assess the structure and strain of thick W coatings as those parameters influence the adhesion on various substrates. This paper describes the status of investigations of strain in thick films of tungsten. Glancing incidence X-ray diffraction can be used to study W polycrystalline textured films, obtain information about their structure, and establish a depth profiling of residual strain. The actual strain at different depths within the coating can be extracted from the measured averaged strain using the inverse Laplace transform method applied to a set of measurements at different angles of the impinging X-ray beam. Results of measurements on films of different thicknesses are discussed.